Strengthening the Locality of Cultural Tourism Destination on Library Design : From the Perspective of Neo-Vernacular Architectural Theories - Irawati, Novi; Prasetyo, Hendi (EMARA: Indonesian Journal of Architecture, 2026)
Contemporary libraries have evolved beyond their traditional role as repositories of knowledge into multifunctional public spaces that support cultural and tourism development. However, limited studies have examined how architectural design, particularly neo-vernacular architecture, can strategically strengthen local identity while enhancing the attractiveness of libraries as cultural tourism destinations. This study aims to investigate the role of neo-vernacular architectural principles in transforming library design into a medium for reinforcing locality and promoting cultural tourism. A qualitative research approach was employed through literature review, comparative case studies, and semi-structured interviews with architects and library managers. The findings reveal that the integration of local materials, traditional architectural forms, passive environmental strategies, and digital technologies significantly enhances cultural representation, spatial experience, and environmental performance. Furthermore, this study identifies five emerging elements in neo-vernacular library development: (1) smart technology integration, (2) participatory design, (3) local economic activation, (4) global-local design balance, and (5) sustainability-oriented strategies. These findings position neo-vernacular architecture not merely as an aesthetic approach but as an integrative design framework that connects architecture, culture, and tourism, enabling libraries to function as cultural landmarks and drivers of local identity.